Dislalia funcional y su influencia en la autoestima de los niños de 5 a 12 años del barrio La Chonta de la parroquia Jimbilla del cantón Loja, periodo 2020-2021. - León Cabrera, Laura Stefania (2022)
The present investigation called: Functional Dyslalia and its influence on the Self-esteem of children from 5 to 12 years of age in the La Chonta neighborhood of the Jimbilla parish of the Loja canton, period 2020-2021, had as a general objective: To determine the influence of functional dyslalia in the self-esteem of children from 5 to 12 years of age in the La Chonta neighborhood of the Jimbilla parish of the Loja canton, it was a descriptive research study with a mixed approach, the design was non-experimental; the methods that were used were descriptive, scientific and analytical-synthetic, for the information collection process the following instruments were used, such as: Survey for parents, Language articulation test (Adapted from the Melgar test) and the Self-esteem scale (Lucy Reidl), the survey was applied to 10 parents and the tests were applied to 10 children. In the results obtained, it was evidenced that children with functional dyslalia affect their self-esteem, which is why parents are recommended that once they identify any difficulty in articulating the children's language, they can refer them to a therapy of language.